Starting MOOCs in African University: The experience of cadi ayyad university, process, review, recommendations, and prospects - Idrissi Jouicha, Abdellah; Berrada, Khalid; Bendaoud, Rachid; Machwate, Said; Miraoui, Abdellatif; Burgos, Daniel (IEEE Access, 2020)
The increasing number of enlistees claiming their right to enroll in the programs of African Universities and the limited number of Higher Education Institutions (HEIs) were the prime reasons of students overcrowding in classes. Massive Open Online Courses (MOOCs) showed a potential to help limiting the challenges of massification in open access HEIs. As the literature review of the MOOC situation in Africa is still nascent, we will qualitatively share the experience of Cadi Ayyad University in Marrakech, Morocco (UCA) in launching a MOOC for its learners as a case study. Created in 2013, this MOOC was entitled UC@MOOC and appeared to respond to the challenges of massification in open access HEIs and the language difficulties faced by students. We will also present an overview of this project, its achievements and the quantity of knowledge delivery it accomplished. This MOOC experience attracted learners from other countries. And we have found that a shortage of MOOCs in Africa drove learners from other African francophone countries to learn from UC@MOOC. Yet a low-cost MOOC with certain limitations such as the weak ICT infrastructure available to the African public will thrive if operated using a MOOC platform and boosted its financial means.
Keywords: Africa; blended learning; e-learning; MOOC; massification; Scopus; JCR